Perancangan Struktur Hydraulic Crane ASTM A871-65 Kapasitas 250 Kg sebagai Sarana Penunjang Laboratorium Outboard Engine di PPNS - Andita Dharmayanti Fatimatu Zahro; Pranowo Sidi; Widya Emilia Primaningtyas (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
The PPNS outboard engine laboratory is one of the learning media for marine engineering majors, it has a practical support tool for the process of moving machines outside the hull of the ship using manual material handling, it's just that it has dimensions that are not in accordance with the conditions of the laboratory layout. So it is necessary to redesign the tool to facilitate the transfer of the outboard engine from the laboratory to the test pool. A hydraulic crane with a capacity, strength and dimensions that are tailored to the needs of the outboard engine laboratory. The calculation and planning of the hydraulic crane structure made from ASTM A871-65 material using the design method has been carried out. The result is a detailed working drawing (detail drawing) with tool dimensions specifications 1526x867x1580 mm made from ASTM A871-65. On the boom hydraulic crane, the maximum stress compared to the allowable stress of the safe/strong material is 164,014 N/mm2 < 298,667 N/mm2, the support structure is safe from bending because the loading force is greater than the working force of the support at 5747005,567 N > 5559,82731 N, at leg structure calculation of safe crane stability where the length of the boom is shorter than the length of the leg (fork), there is no disturbing moment. The total budget plan for making tools is Rp. 1,992,000. The data from the design and budget plan are used as guidelines for the manufacture of hydraulic cranes.